(3GdeSGFd GdMcejIs - (3GdMSjf Hf YHO Gddg Hf GdMSf Hf Ydj Hf SjfG , CHh Ydj GdnHrdNqj Ke GdoHNGQqj GdeYQha HGHf SjfG, (B427 (3g`s
(3ChdgG (B:s
(3e de cGf hLhO cd TF GdNGU Hg hgh hMOJg L dCf cd hGMO ef GdehLhOGJ GfeG gh hGMO ef GdehLhOGJ s
(3BNQgG (B:s
(3de jcf ddVhA bhGe hdG hLhO aGMJjL Gf jchf LQe ZjQ eTa hde jUdM dg LQe ZjQ GdGQV s
(3bQf GdfSN (B:s
(3GdbQf GdSGOSs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B241s
(3eUOQ GbJfGA GdCUd (B:s
(3eLdS ThQGi (B(599) s
Keywords: (3GdadSaI hGdefWbs